Live Streaming Shopping: a Powerful Solution to Increase Visibitility and Sales Conversion - Nursafitri, Sintia; Angriani ZN, Sefrimel (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to analyze the effect of live streaming shopping on increasing brand visibility and sales conversion. The phenomenon of live streaming shopping has become a significant trend in the e-commerce industry, but there is still limited research that comprehensively examines the factors that influence its effectiveness. This study uses a quantitative approach with a survey method on 400 respondents selected through a purposive sampling technique. The independent variables in this study include Live Streaming Quality (X1), Host-Audience Interaction (X2), Promotion Discount (X3), and Platform Features (X4), while the dependent variables are Brand Visibility (Y1) and Sales Conversion (Y2). Data analysis uses multiple linear regression techniques with the help of SPSS 26.0 software. The results show that all instruments are valid and reliable, with normally distributed data. The partial test (t-test) proves that all independent variables have a positive and significant effect on both dependent variables, with Host-Audience Interaction having the strongest effect on Sales Conversion (t-count = 4.514, sig. 0.000). The simultaneous test (F test) shows that the four independent variables together have a significant effect on Brand Visibility (F = 23.456, sig. 0.000) and Sales Conversion (F = 28.734, sig. 0.000). The coefficient of determination shows that the model can explain 39.3% of the variation in Brand Visibility and 44.2% of the variation in Sales Conversion. This study concludes that live streaming shopping is a powerful solution to increase brand visibility and sales conversion, with host- audience interaction as a key success factor. These findings provide strategic implications for businesses to optimize the implementation of live streaming shopping through improving streaming quality, engaging interactions, attractive promotional strategies, and developing user-friendly platform features